Ethnomathematics-Based Student Worksheets Assisted by Augmented Reality (AR) GeoGebra to Improve Mathematics Learning Outcomes - Buchori, Achmad; Rahmawati, Noviana Dini; Anggraina, Nabila; Khoiri, Nur (Journal of Innovation in Educational and Cultural Research, 2026)
This study aimed to develop and evaluate ethnomathematics-based student worksheets assisted by Augmented Reality (AR) GeoGebra to enhance students' understanding of three-dimensional geometry. Using a Research and Development (RD) approach with the ADDIE model, the student worksheet was validated by media and material experts, tested for practicality through student response questionnaires, and evaluated for effectiveness using N-Gain analysis based on pre-test and post-test results. Thirty-one junior high school students participated, divided into an experimental class (n = 15) and a control class (n = 16). The developed student worksheet demonstrated high validity—88.33% from the media expert and 91.28% from the material expert—and excellent practicality (88.13%). The experimental class achieved a higher N-Gain score of 0.78 (high category) than the control class's 0.48 (moderate category), with the difference significant at the 0.05 level. These findings indicate that the AR-integrated GeoGebra student worksheet is valid, practical, and effective in improving students' conceptual understanding and learning outcomes, offering a meaningful integration of technology and culture in mathematics education.